The Pivot of Civilization - Sanger, Margaret, 1879-1966; Wells, H. G. (Herbert George), 1866-1946 (Salt Lake City, UT : Project Gutenberg, 2006)
"The Pivot of Civilization" by Margaret Sanger is a thought-provoking social and political treatise, likely written in the early 20th century. The book discusses the critical importance of birth control as a fundamental aspect of modern civilization, exploring the implications of uncontrolled reproduction on society's welfare and progression. The opening of the work sets the stage by introducing Sanger$1 (Bs perspective on the duality of civilization: one rooted in traditional values that restrict individual freedoms, and the other advocating for scientific inquiry and the control of human instincts, particularly concerning sexuality. Sanger reflects on her personal experiences and observations, arguing that true progress can be achieved only through empowering individuals$1 (Bespecially women$1 (Bby allowing informed family planning. She critiques existing social structures and norms that perpetuate ignorance and suffering, asserting that the liberation of women from the burdens of unplanned motherhood is essential for social and economic advancements. (This is an automatically generated summary.)s
Release date is 2006-02-22
Produced by An Anonymous Volunteer, Dan Muller, and David Widger
Keywords: Birth control